2017
DOI: 10.1371/journal.pcbi.1005407
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the axon membrane skeleton structure and implications for its mechanical properties

Abstract: Super-resolution microscopy recently revealed that, unlike the soma and dendrites, the axon membrane skeleton is structured as a series of actin rings connected by spectrin filaments that are held under tension. Currently, the structure-function relationship of the axonal structure is unclear. Here, we used atomic force microscopy (AFM) to show that the stiffness of the axon plasma membrane is significantly higher than the stiffnesses of dendrites and somata. To examine whether the structure of the axon plasma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 56 publications
7
81
1
Order By: Relevance
“…We show that axonal actin rings are made of a small number of long, intertwined filaments rather than by a large number of short, bundled filaments as previously hypothesized Unsain et al, 2018b;Xu et al, 2013;Zhang et al, 2017). This short filament model was inferred from the presence of adducin at actin rings, at least along the distal axon Xu et al, 2013), because adducin was described as a capping protein that can bind to the barbed end of filaments (Kuhlman et al, 1996).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We show that axonal actin rings are made of a small number of long, intertwined filaments rather than by a large number of short, bundled filaments as previously hypothesized Unsain et al, 2018b;Xu et al, 2013;Zhang et al, 2017). This short filament model was inferred from the presence of adducin at actin rings, at least along the distal axon Xu et al, 2013), because adducin was described as a capping protein that can bind to the barbed end of filaments (Kuhlman et al, 1996).…”
Section: Discussionsupporting
confidence: 68%
“…Finally, the arrangement of actin rings as a braid of long filaments is relevant to the observed stability of the MPS: closely apposed, intertwined filaments are likely to be resistant to severing factors such as ADF/cofilin (Michelot et al, 2007), and further stabilized by their embedding in the spectrin mesh. Rings made of long intertwined filaments are likely to be stiffer than bundled short filaments, hence could form the rigid part of a flexible and resistant scaffold when linked by elastic spectrins (Zhang et al, 2017), explaining the role of the MPS in the mechanical resistance of axons (Krieg et al, 2017). Beyond shedding light on the molecular underlaying of the MPS function, the ultrastructural insights obtained here could help understand its potential dysfunctions in neurodegenerative diseases, where the axonal integrity is often affected first (Encalada and Goldstein, 2014;Sleigh et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…61 These elements were assigned a shear modulus G = 0.0016 MPa and a viscosity η =10 5 Pas. 62,63 Mechanical properties of all the model components can be found in Table 1. In a recent study, fluid friction was observed at the membrane-cortex interface with friction forces being proportional to the relative speed of the two layers.…”
Section: Methodsmentioning
confidence: 99%
“…autophagosomes 8 or mitochondria 9 , has been observed by super-resolution microscopy and 2D-electron microscopy (EM) in both normal and degenerating axons 10, 11 . Considering the spatial limitation exerted by the rigid axon membrane 12 , the trafficking of large cargoes is likely to be affected. In fact, a simulation study based on axon structure and intra-axonal microfluidic dynamics predicted that cargo trafficking was impeded by the friction from the axonal walls in small-calibre axons 13 .…”
Section: Introductionmentioning
confidence: 99%